THE ADAPTATION METHOD IN TRANSLATING CULTURAL ASPECTS OF THE FAIRY TALE DER RATTENFÄNGER VON HAMELN AND READERS' RESPONSES - Larasati, Larasati; Rosyidah, Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
Adaptation is one of the translation methods that emphasizes the culture of the TL (Targeted Language). The use of adaptation methods can overcome the problem of cultural differences between the text and the readers. This study describes the use of adaptation methods in translating cultural aspects in the German fairy tale Der Rattenfänger von Hameln by Bruder Grimm into Indonesian. In addition, this study describes the reader's response to the fairy tale. This research is descriptive qualitative research. The data sources in this research are the SL fairy tales and TL fairy tales, while the data are words, phrases, sentences that show cultural aspects in the SL and TL fairy tales. In addition, the data are also in the form of words, phrases, sentences that show the response of the TL fairy tale readers in the interview to the TL fairy tales, both to the intrinsic and emotional elements. Data analysis in this study used the four stages of the Miles Huberman (1988) analysis model, data collection, data reduction, data presentation, and verification or conclusion making. The results show that there are four out of five aspects of Newmark's cultural categories in SL fairy tales, namely aspects of ecological culture, material culture, social culture, and socio-political and administrative organizational culture. The reader's response to the TL fairy tales is generally good and shows the Bsa fairy tales can be understood and received well.